Impact of COVID-19 lock-down period on orthopedic and trauma surgical activity in a northern Italian hospital - Turati, Marco; Gatti, Simone; Rigamonti, Luca; Zatti, Giovanni; Munegato, Daniele; Crippa, Marco; Benedettini, Erik; Piscitelli, Daniele; Bigoni, Marco; Turati, Riccardo (Frontiers in Medicine, 2024)
Objectives: This study aims to describe the impact of Covid-19 on Orthopedic and Trauma surgical activity in a single level-I trauma center in Northern Italy during the lockdown period. We proposed comparing surgical procedures performed during the outbreak and in the same period the previous year. Methods: In this single-center retrospective epidemiological cohort study, the “lockdown cohort” of patients who were treated from March 1st to May 24th, 2020, was compared to the “control cohort” who received treatment during the same period in 2019. The primary outcome was to evaluate the differences between the lockdown and control cohorts regarding surgical volumes. The secondary outcome was to evaluate any differences in the type of surgical procedures performed in the two cohorts in the elective and emergency setting. Results: Orthopedic surgical activity has suffered a global reduction of 72.4% during the lockdown period (from 36 ± 6.1 to 10.7 ± 8.4 per week; p<0.01), with the ratio of emergency to elective operations increasing from 0.7:1 in 2019 to 3.3:1 in 2020. Elective surgery has in fact been almost completely suspended and was affected with a reduction of 88.9% (from 20.8 ± 5.2 to 4.3 ± 2.8 cases per week; p<0.01), while emergency trauma surgery suffered a 49.7% reduction (from 15.1 ± 3.2 to 8.2 ± 6.1 cases per week; p<0.01). Conclusion: The Covid-19 outbreak severely affected the Italian national health system, and Lombardy was the region most affected. The 2020 Covid-19 lockdown has heavily conditioned our Orthopedic and Trauma department surgical activity.